Building Resilience, Equity and Opportunity in Myanmar : The Role of Social Protection -- Overview - World Bank Group (Washington, DC, 2015)
Myanmar is a country in transition and faces the following main challenges: a) reducing the incidence of poverty and improving human development outcomes, particularly for the poor and vulnerable; and b) addressing the insecurity of incomes and developing mechanisms to reduce exposure to risks and ability to cope with ill-health, disasters, and other shocks. Social protection policies and programs can play an important role in Myanmar’s strategy for poverty reduction and people-centered development. Many countries have used a range of programs to achievetheir development goals, particularly on poverty reduction and inclusive growth. An effective social protection system can help the poor and vulnerable better manage the opportunities and risks arising from the ongoing reforms, and can help promote household and community resilienceand social cohesion.